Two) Given The Polynomials: Elaborated By: Neitan Urbano and Maira Urbano

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 5

ELABORATED BY:

NEITAN URBANO

AND MAIRA URBANO

Two) given the polynomials


P( x )=3 x 3+ 4 x 2 +2 x +2

q(x)= 2 x2 + x +2

r(x)= 3 x 2−2 x −2

 P(x) * q(x) * r(x)

p(x)q(x)= (3 x 3+ 4 x 2 +2 x +2)(2 x2 + x +2)

3 x 3=2 x2 + x +2 = 6 x 5+ 3 x 4+ 6 x3
4 x2 =2 x 2 + x+ 2= 8 x 4 + 4 x 3+ 8 x 2
2 x=2 x2 + x +2= 4 x3 +2 x 2+ 4 x

2=2 x2 + x +2= 4 x2 +2 x+ 4

=6 x 5+ 11 x 4 +14 x 3+14 x2 +6 x +4

P(x)q(x)* r(x)= (6 x 5+ 11 x 4 +14 x 3+14 x2 +6 x +4 ¿(3 x 2−2 x −2)

6 x 5=3 x 2−2 x −2=18 x 7−12 x 6 −¿12 x 5

11 x 4=3 x 2−2 x−2=33 x 6−¿22 x 5−22 x 4


14 x 3=3 x 2−2 x −2= 42 x 5−28 x 4−¿28 x 3

14 x 2=3 x 2−2 x−2=42 x 4 −¿28 x 3−28 x 2


6 x =3 x 2−2 x −2= 18 x 3−12 x2 −12 x

4=3 x 2−2 x−2= 12 x2−8 x −8


=18 x 7+ 21 x 6 + 8 x 5−8 x 4 −¿38 x 3−28 x 2−20 x−8

 3p(x)*2q(x)+5r(x)
3p(x)=3 ¿) = 9 x 3+ 12 x 2 +6 x+ 6

2q(x)=2 ¿)= 4 x2 +2 x+ 4

5r(x)= 5 ( 3 x 2−2 x −2 )=15 x 2−10 x−10

3p(x)*2(x)= (9 x 3+ 12 x 2 +6 x+ 6)(4 x2 +2 x+ 4 )

9 x 3=4 x2 +2 x+ 4 =36 x 5−18 x 4−36 x 3


12 x2=4 x2 +2 x+ 4 =48 x 4 −¿24 x 3−48 x 2
6 x =4 x2 +2 x+ 4 =24 x 3−12 x2 +24 x

6 =4 x2 +2 x+ 4 =24 x 2 +12 x +24

=36 x 5+ 66 x 4 +84 x 3 +84 x 2 +36 x+24

3p(x)* 2q(x)= 36 x 5+ 66 x 4 +84 x 3 +84 x 2 +36 x+24

+ 5r(x)= 15 x 2−10 x−10

36 x 5+ 66 x 4 +84 x 3 +99 x 2+26 x +14

 3p(x)*2q(x)+5r(x)+r( x)2

=(36 x 5+ 66 x 4 +84 x 3 +99 x 2+26 x +14 )+(3 x 2−2 x −2¿ ¿ 2

(36 x 5+ 66 x 4 +84 x 3 +99 x 2+26 x +14 ¿+(9 x 4 −4 x 2−4)

=36 x 5+ 75 x 4 + 84 x 3+ 95 x2 +26 x +10

3q( x) 5r(x)
 * + r( x )2
2 3
3q(x)
=2 x2 + x +2=6 x 2 +3 x 2+6
2
5r(x)
=3 x 2−2 x −2=15 x 2−10 x−10
3
3q( x) 5r(x)
* = ¿)(15 x 2−10 x −10)
2 3
6 x 2=15 x 2−10 x −10=90 x 4 −60 x 3−60 x 2

3 x 2=15 x2 −10 x−10 =45 x 3−30 x 2−30 x


6 =15 x 2−10 x −10=90 x 2−60 x−60

=90 x 4 −15 x 3−4 x 2−90 x−60+ ( 9 x 4−4 x 2−4 )

=99 x 4 −15 x 3−4 x 2−90 x−64

15
=( 99 x 4 −15 x3 −4 x 2−90 x−64)=
6
1485 4 225 3 30 2 1350 960
x −¿ x− x− x−
6 6 6 6 6

three.) given the polynomials


p(x)= 5 x 4 +3 x 3+ 4 x 2 +2 x −2

q(x)= 3 x 2+ 2 x−2

r(x)=3 x 3+ 2 x 2 +2 x−2

 3p(x)−¿4q(x)+5r(x)

p(3)=5(3 ¿ ¿4 +3(3 ¿ ¿3 +4 ¿+ 2(3)−2

p(3)=5*81+3*27+4*9+6−2

=405+81+36+6−2=526

q(4)=3(4 ¿2 +2(4 )−2

q(4)=3*16+8−2

=48+8−2=54

r(5)=3(5 ¿ ¿3 +2 ¿
r(5)=3*125+2*25+10−2

=375 + 50 + 10 −2= 433

3p(x) – 4q(x) +5r(x)=

=526 −54 + 433

= 472+ 433
= 905

3 p( x) 5 r (x )
 −4 q ( x )+
2 3
526 433
−54+
2 3
1578 324 866
− + =
6 6 6
1254 866
+ =
6 6
2120
=
6

5 r (x)
 3p(x)−4 q ( x )−
2
433
526−54−
2
1052 108 433
− −¿
2 2 2
511
=
2

Thank you very much ;)

You might also like